The role of dissemination and implementation science in global breast cancer control programs: Frameworks, methods, and examples. - Rositch, Anne F.; Unger‐Saldaña, Karla; DeBoer, Rebecca J.; Ng'ang'a, Anne; Weiner, Bryan J.; Unger-Saldaña, Karla (Cancer (0008543X))
Global disparities in breast cancer outcomes are attributable to a sizable gap between evidence and practice in breast cancer control and management. Dissemination and implementation science (D&IS) seeks to understand how to promote the systematic uptake of evidence-based interventions and/or practices into real-world contexts. D&IS methods are useful for selecting strategies to implement evidence-based interventions, adapting their implementation to new settings, and evaluating the implementation process as well as its outcomes to determine success and failure, and adjust accordingly. Process models, explanatory theories, and evaluation frameworks are used in D&IS to develop implementation strategies, identify implementation outcomes, and design studies to evaluate these outcomes. In breast cancer control and management, research has been translated into evidence-based, resource-stratified guidelines by the Breast Health Global Initiative and others. D&IS should be leveraged to optimize the implementation of these guidelines, and other evidence-based interventions, into practice across the breast cancer care continuum, from optimizing public education to promoting early detection, increasing guideline-concordant clinical practice among providers, and analyzing and addressing barriers and facilitators in health care systems. Stakeholder engagement through processes such as co-creation is critical. In this article, the authors have provided a primer on the contribution of D&IS to phased implementation of global breast cancer control programs, provided 2 case examples of ongoing D&IS research projects in Tanzania, and concluded with recommendations for best practices for researchers undertaking this work.